491. Clinical Manifestations and Outcomes of Clostridium difficile Infection in Long-Term Care Patients: An 8-Year Retrospective Cohort Study. (26th November 2018) - Chandramohan, Suganya; Krishna, Amar; Virdi, Parminder; Polistico, Jordon; Thammineni, Nikhila; Mehar, Anupamdeep Singh; Gill, Angad Singh; Saleem, Aleena; Javed, Ibtehaj; Qaryoute, Dania; Deporre, Daniel; Zhang, Pingping; et al.
Abstract: Background: Residents of long-term care facilities (LTCF) have high risk of Clostridium difficile infection (CDI) and its associated adverse outcomes. We describe the clinical characteristics and outcomes of CDI in LTCF patients admitted to an acute care (AC) hospital. Methods: This is a descriptive retrospective study of CDI patients admitted to Detroit Medical Center (DMC) from LTCF from January 2009 to December 2017. Patients identified through chart review as having CDI on admission or within 48 hours of admission and without recent AC hospitalization in the prior 4 weeks were included. CDI and CDI severity were defined based on 2017 clinical consensus guidelines. Definitions: CDI-Either presence of diarrhea or evidence of ileus or megacolon and either presence of C. difficile toxin in stool or evidence of pseudomembranous colitis. Severe CDI-Presence of white blood counts ≥15, 000 and serum creatinine >1.5 mg/dL. Complicated CDI-Presence of either toxic megacolon, sepsis, systemic inflammatory response syndrome, colonic perforation, or requiring ICU admission. Demographics, medical conditions, laboratory results, prior 60-day antibiotic use, CDI treatment, and outcomes were collected. Patients' follow-up extended 90 days; however, data were limited to hospital charts from index admission or readmission to the same hospital. Results: Among the 85 patients who met the inclusion criteria, 45 (53%) were female, the mean age was 76 (SD: 16), and the median Charlson index score was 6 (range: 4–8). The common source of prior 60-day antimicrobial exposure was β-lactam/β-lactamase inhibitors (39%), Flagyl (15%), vancomycin (18%). The majority of patients were treated with flagyl (71%), 41% with vancomycin and 17% with concurrent or sequential flagyl and vancomycin. Majority of CDI patients (56%) experienced severe CDI with 25% experiencing complicated CDI. During the 90-day follow-up period, 32% of patients required readmission (within 30 days of discharge) for recurrent CDI and 15% of patients died in the hospital. Conclusion: CDI patients admitted to DMC from LTCF experience considerable clinical burden. Further research is warranted toward understanding the burden of CDI among LTCF patients admitted to AC facilities. Disclosures: S. Chandramohan, Pfizer Inc.: Collaborator, Research grant. P. Zhang, Pfizer Inc.: Employee, Salary. K. Heinrich, Pfizer Inc.: Employee, Salary. E. Gonzalez, Pfizer Inc.: Employee, Salary. T. Chopra, Pfizer Inc.: Collaborator, Research grant.